The Influence Of Sıtuatıonal Leadershıp Style On Employee Performance Through Job Satısfactıon - Sunarni Sunarni; Eko Priyo Purnomo; Mai Yuliza; Ignatius Erik Sapta Yanuar (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study delves into the intricate relationships among Job Satisfaction, Situational Leadership, and Employee Performance in organizational settings. The research offers vital insights into these critical aspects of workplace dynamics. First and foremost, the study confirms the significant influence of Job Satisfaction on Employee Performance. It reiterates the well-established fact that contented employees tend to perform better. Organizations are urged to prioritize initiatives aimed at boosting job satisfaction to enhance overall employee performance, leading to increased productivity and organizational success. Secondly, the research unveils an intriguing finding: Situational Leadership, when examined independently, does not directly impact Employee Performance. However, Situational Leadership emerges as a vital factor in shaping Job Satisfaction. This underscores the paramount importance of leadership adaptability and its role in fostering a positive work environment, ultimately contributing to employee contentment. Moreover, when considering Situational Leadership, Job Satisfaction, and Employee Performance collectively, a robust and positive relationship emerges. This highlights the interconnected nature of these variables, emphasizing the need for organizations to adopt a holistic approach to leadership and employee management. In conclusion, this study provides organizations with valuable insights into optimizing their leadership strategies to enhance employee performance. It underscores the significance of nurturing job satisfaction and cultivating adaptable leadership styles to create a conducive work environment, fostering employee contentment, and, consequently, organizational triumph. Future research may delve deeper into contextual factors to refine these relationships further, offering even more precise guidance for organizations in optimizing their strategies for employee performance and satisfaction.